2017
DOI: 10.1016/j.ijppaw.2017.03.007
|View full text |Cite
|
Sign up to set email alerts
|

The diversity and impact of hookworm infections in wildlife

Abstract: Hookworms are blood-feeding nematodes that parasitize the alimentary system of mammals. Despite their high pathogenic potential, little is known about their diversity and impact in wildlife populations. We conducted a systematic review of the literature on hookworm infections of wildlife and analyzed 218 studies qualitative and quantitatively. At least 68 hookworm species have been described in 9 orders, 24 families, and 111 species of wild mammals. Black bears, red foxes, and bobcats harbored the highest dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
67
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 178 publications
(182 reference statements)
1
67
1
1
Order By: Relevance
“…Additionally, a higher proportion of hookworm‐infected pups engaged in swimming compared to noninfected pups. These observations are the opposite of our predicted impact of hookworms in the development of swimming skills given the known effects of hookworms on body mass and hemoglobin levels (Seguel & Gottdenker, ). An alternative explanation for these results can be given by a potential compensatory mechanism deployed by fur seal pups with hookworm infection.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…Additionally, a higher proportion of hookworm‐infected pups engaged in swimming compared to noninfected pups. These observations are the opposite of our predicted impact of hookworms in the development of swimming skills given the known effects of hookworms on body mass and hemoglobin levels (Seguel & Gottdenker, ). An alternative explanation for these results can be given by a potential compensatory mechanism deployed by fur seal pups with hookworm infection.…”
Section: Discussioncontrasting
confidence: 97%
“…However, detecting these dynamics in natural systems is challenging because the impact of parasites on host populations is sometimes subtle and difficult to document (Pedersen & Fenton, ). These subtle or “hidden effects” of parasitism are hard to measure because they are associated with changes in behavior and physiological variables which may be affected by factors other than parasitism (e.g., diet, maternal care, genetics) (Carlsson et al, ; Higgins & Gass, ; Seguel & Gottdenker, ). Additionally, the changes in an animal physiology and health status due to parasitism are related not only to the parasite but also to the host response to the infection (Ezenwa et al, ; Fox, ; Seguel et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, juveniles in our study population with low growth rates in the first 6 months of life have a lower probability of survival to adulthood than those with high growth rates (Hofer & East, ). High Ancylostoma infection loads are energetically costly because of substantial blood loss and damage to the intestinal wall (Urquhart et al, ), and have been reported to retard juvenile growth, and cause anemia and malnutrition in other mammals (Sakti et al, ; Seguel & Gottdenker, ; Stoltzfus et al, ). This suggests that the energetic cost of high Ancylostoma infection loads in rapidly growing, milk‐dependent juvenile hyenas may compromise growth and thus curtail survival to adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Our study aims to investigate determinants of both Ancylostoma (nematode) and Cystoisospora (coccidian) infection loads in high‐ranking and low‐ranking juvenile spotted hyenas and to assess the resistance and tolerance of juveniles in these two social categories to parasite infection. We focus on Ancylostoma and Cystoisospora because both have direct life cycles that need no intermediary host, both cause damage to the epithelial lining of the small intestine, and are considered energetically costly parasites (East et al, ; Seguel & Gottdenker, ; Shrestha et al, ). We test predictions derived from six hypotheses: (a) the resource allocation hypothesis of life‐history theory expects high‐ranking juveniles to have lower infection loads than low‐ranking juveniles, because they should have more resources to allocate to immune processes.…”
Section: Introductionmentioning
confidence: 99%